The Main Function Of Drilling Fluid In Oil And Gas Well Drilling And Its Selection Depending On The Formation - Aziz Abdikarimovich Mansurov (Genius Journals, 2025)
Drilling fluid is a key element of the drilling system, providing load-bearing, transport, isolation, and information-diagnostic functions. The purpose of this paper is to systematically describe the main functions of drilling fluid and propose a scientifically based approach to its selection depending on the geological and technical conditions and properties of the target formation. The study provides a review of modern fluid classes (water- and oil/synthetic-based), their rheological and colloidal-chemical properties, and an analysis of critical scenarios: swelling clay formations, cavernously fractured carbonates with absorptions, salt formations, HPHT intervals, zones with H₂S/CO₂, water-cut and decompressed reservoirs. A multi-level selection methodology is proposed using (i) a geohazards decision matrix, (ii) laboratory tests (shale swelling, HPHT filtration, friction and lubrication, formation water/oil compatibility), (iii) hydraulic modeling (ECD, cuttings breakdown velocity, pressure profile), and (iv) an environmental and economic assessment of the full life cycle. The results are presented in the form of practical recommendations for the selection of formulations and modes for typical lithotypes. Limitations and directions for further research, including digital drilling twins and adaptive drilling fluids, are discussed
Keywords: Drilling fluid; functions; selection